ANALISIS PENGARUH ACCRUAL DAN REAL EARNINGS MANAGEMENT TERHADAP CORPORATE ENVIRONMENTAL DISCLOSURE DAN MEKANISME CORPORATE GOVERNANCE SEBAGI VARIABEL PEMODERASI - Niar Azriya; Jerry Bastian; Septia Uswatun Hasanah (Universitas Sang Bumi Ruwa Jurai, 2018)
The purpose of this research is to examine of the effect of accrual and real earnings management on corporate environmental disclosure and corporate governance as moderation variable. The variabel accrual earnings management measure use discretionary accrual and abnormal cash flows from operating, abnormal production costs, and abnormal discretionary expenses measured for real earnings management with Roychowdhury (2006) model. Variable corporate governance measured use proportion of indendent commissioners, the number of audit committee members, and the size of the board of directors.For corporate environmental disclosure variabel measured with Index Clarkson, et al (2013). Sampel in this research is 97 companies. The result shows accrual and real earnings management has no significant effect on corporate environmental disclosure. But the effect of moderate proportion indendent commissioners to accrual earnings management on corporate environmental disclosure show the confirmed hypothesis proposed.